Penatalaksanaan Fisioterapi Pada Kasus Low Back Pain Myogenic Di Rsud Dr Moewardi Surakarta - Denny Arista, Petra; , Sugiyono, S.Fis,M.H. (Kes ) (2015)
Background: Low Back pain (LBP) is including one of the trouble musculoskeletal, psychological trouble and effect of wrong mobilization. LBP cause incidence of feeling stiff, rheumatic pain, stiff, or is not delicious at area lumbal of following sacrum. Physiotherapy in this case plays a part to return and overcome the impairment and the activity limitation, so that activity patient can return without existence of sigh for example by modality physiotherapy that is IR, TENS and practice therapy (William Flexion Exercise) to overcome the problem of low back pain. Purpose: to know the figure about management of Infra Red, TENS and William Flexion Exercise at low back pain myogenic condition. Result: After therapy about six times get obtained results of pain evaluation with at quite painful T0 : 5 to T5 : 2, tenderness painful T0 : 6 to T5: 4 and motion painful T0 : 7 to T5 : 5. Hinge movement limitedness evaluation result with LGS trunk used ribbon measure at flexi T0:7 cm to T5: 8 cm, extension T0 : 4 cm to T5 : 5 cm, eight side flexi T0 : 13 cm to T5 : 14 cm, and left side flexi T0 : 13 cm to T5 : 14 cm. results of the assessment of muscle strength by MMT at flexor trunk T0 : 3 to T5 : 4 and at extensor trunk T0 : 4 to T5 : 4. Functional activity ability with Oswestry (ODI%) T0 : 30% to T5 : 22%. Conclusion: Infra Red can decrease painful, TENS useful to increasing strength muscle and Exercise Therapy useful to decrease scope move joint.